(untitled) (International Journal of Management and Sustainability, 2014)
Aquaculture is becoming a very important source of income to many people as well as a source of protein in their diets. This study examined the influence of the entrepreneur and enterprise characteristics on small-scale cage fish enterprises in the Asuogyaman and South Dayi Districts. The research employed a descriptive-correlation survey design, which used quantitative method to collect data from 105 owners and managers of small-scale cage fish enterprises. The findings revealed that age of entrepreneurs influenced customer satisfaction as entrepreneurs experience also influenced growth in sales. It was observed that technical know-how, attitude towards work, and managerial skills, had a significant relationship with profitability, and customer satisfaction. Finally, age of the enterprise was found to have a significant relationship with growth in sales. In conclusion, all the variables had positive relationships with enterprise success, but not all the relationships were significant. It is recommended that cage fish farmers should be encouraged to invest more in technical education, which will help improve on the success of their enterprises. Furthermore, farmers should take precautions to reduce the risk of failure to increase their chances of success and survival.